2020
DOI: 10.1097/mao.0000000000002648
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Effectiveness of Eustachian Tube Balloon Dilatation for Patients With Eustachian Tube Dysfunction—Evaluation in a Pressure Chamber

Abstract: Introduction: The Eustachian tube plays a crucial role in pressure equalization between the middle ear and ambient pressure for fast and large pressure differences. In patients with chronic Eustachian tube dysfunction, Eustachian tube balloon dilatation is increasingly used as surgical therapy. Subjectively, many patients report an improvement of the symptoms postoperatively. Hence, there is a need to objectively measure this effect. Methods: The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 31 publications
0
30
0
1
Order By: Relevance
“…There were nine prospective studies (three case‐control, six cohort studies) encompassing 1336 patients with CRS and patients with CRS and ETD (CRS+ETD) 1,8–15 . There were seven studies (one RCT, four prospective case series, and two retrospective case series) including 161 patients with primary ETD 3,16–19 2122. Risk of bias assessment can be found in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…There were nine prospective studies (three case‐control, six cohort studies) encompassing 1336 patients with CRS and patients with CRS and ETD (CRS+ETD) 1,8–15 . There were seven studies (one RCT, four prospective case series, and two retrospective case series) including 161 patients with primary ETD 3,16–19 2122. Risk of bias assessment can be found in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…9,16 Recently, balloon dilation of the cartilaginous ET has shown encouraging results. Jansen et al 17 described significant improvement in symptoms in 23 ears at 4 weeks postoperatively. Formánek et al 18 described significant improvements in ETDQ-7 scores in all 14 ears at the 12-month follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…9,16 Recently, balloon dilation of the cartilaginous ET has shown encouraging results. Jansen et al 17 In this study, we performed electrocoagulation tuboplasty to treat patients with chronic ETD. Although the proportion of patients with normalized ETDQ-7 scores was not significantly different between the groups at 6 months posttreatment, the difference was significant between the groups at 12 months posttreatment.…”
Section: Discussionmentioning
confidence: 99%
“…These findings point to the efficacy of dual surgical procedures and to the superadded benefit of BET on the outcome of FESS for management of ETD. Similarly, Meyer et al [32] reported improvements in the ETDQ-7 scores after balloon dilation and Jansen et al [33] documented that ET balloon dilatation significantly reduced ET opening pressure with significant improvement in symptoms as judged subjectively by ETDQ-7. Also, Froehlich et al [34], out of a systematic literature review for the effectiveness of ET balloon dilation for treatment of ETD, reported significantly decreasing ETDQ-7 scores and improving tympanogram with normal otoscopic findings and positive Valsalva maneuver.…”
Section: Chronic Rhinosinusitis [Crs] Especially If Associated With Nasal Polyposis [Crswnp]mentioning
confidence: 91%